Building new democracies : economic and social reform in Brazil, Chile, and Mexico - Duquette, Michel, 1947- (Studies in comparative political economy and public policy, 1999)
"In Building New Democracies Michel Duquette analyses the main public policies of Brazil, Chile, and Mexico to explore examples of how countries make the transition from an authoritarian regime to a democratic society." "The main objective of the book is to follow the process of policy formation in very young democracies."--Jacket